Анализ выживаемости пациентов пожилого и старческого возраста с раком толстого кишечника II-III стадий - Колесник, А. П.; Колесник, И. П.; Кечеджиев, В. В.; Kolesnik, A. P.; Kolesnіk, I. P.; Kechedzhyiev, V. V.; Колеснік, Олексій Петрович; Кечеджиєв, Вячеслав Віталійович (My University, 2019)
Цель исследования. Анализ выживаемости и определение факторов риска, влияющих на продолжительность жизни пациентов пожилого и старческого возраста с раковыми опухолями толстого кишечника II–III стадий. Материалы и методы. Проведен анализ историй болезни 40-ка пациентов пожилого и старческого возраста с впервые диагностированным раком толстого кишечника II–III стадий, прооперированных в Запорожском областном клиническом онкологическом диспансере за 2016 г. Результаты. При анализе выживаемости отмечено, что общая 2-х летняя выживаемость составила 80%. Анализ выживаемости в зависимости от стадии показал, что общая 2-х летняя выживаемость у пациентов со II стадией заболевания составила 91,3%, а у пациентов с III стадией – 64,7% (р < 0,05). Общая 2-х летняя выживаемость у мужчин составила 68,2%, в то время как у женщин – 94,4% (р < 0,05). У больных с локализацией опухоли в правой половине толстого кишечника результаты общей выживаемости были ниже, по сравнению с пациентами с локализацией опухоли в левой половине (62,5% и 91,7%, соответственно, при р < 0,05). Показатели общей 2-х летней выживаемости у больных с I, II, III степенью кровопотери составили, соответственно, 94,4%, 83,3%, 50% (р < 0,05). Purpose of the study. Analysis of the survival and determination of risk factors affecting the life expectancy of elderly patients with II–III stages of colon cancer. Materials and methods. The analysis of case histories of 40 elderly and senile patients with II–III stages of the colon cancer, operated in the Zaporizhzhia Regional Clinical Oncology Dispensary in 2016. Results and discussion. When analyzing the survival rate, it was noted that the overall 2-year survival rate was 80%. The analysis of survival depending on the stage showed that the total 2-year survival in patients with II stage of disease was 91,3%, and among patients with III stage it was 64,7% (p < 0,05). The overall 2-year survival for men was 68,2%, while for women it was 94,4% (p < 0,05). In patients with tumor localization in the right half of the large intestine, overall survival rates were lower compared with patients with tumor localization in the left half (62,5% and 91,7%, respectively, p < 0.05). Indicators of total 2-year survival in patients with I, II, III degree of blood loss were respectively 94,4%, 83,3%, 50% (p < 0,05). The stage of the disease, tumor localization, sex, the degree of intraoperative blood loss, leukocytosis significantly correlate with the overall survival rates in elderly and senile patients with II–III stages of colon cancer(p < 0,05). Further study and search for new prognostic factors of surgical risk in elderly and senile patients with colorectal cancer are needed.
Survival analysis of elderly and senile patients with colon cancer of II–III stages
Keywords: рак толстой кишки; выживаемость; оперативное лечение; лимфодиссекция; лапароскопия; colon cancer; survival; operative treatment; lymphodissection; laparoscopy